Relativistic coupled-cluster study of RaF as a candidate for the parity- and time-reversal-violating interaction - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2016)
We have employed both the Z-vector method and the expectation-value approach in the relativistic coupled-cluster framework to calculate the scalar-pseudoscalar (S-PS) P, T-odd interaction constant W-s and the effective electric field E-eff experienced by the unpaired electron in the ground electronic state of RaF. Further, the magnetic hyperfine structure constants of Ra-223 in RaF and Ra-223(+) are also calculated and compared with the experimental values wherever available to judge the extent of the accuracy obtained with the employed methods. The outcome of our study reveals that the Z-vector method is superior to the expectation-value approach in terms of accuracy obtained for the calculation of ground-state property. The Z-vector calculation shows that RaF has a high Eeff (52.5 GV/cm) and W-s (141.2 kHz), which makes it a potential candidate for the electric dipole moment of the electron (eEDM) experiment. An estimation of uncertainty associated with our final results is made, and it is found that it lies below 10%.